Achmad Yurianto in the frame of online journalism pioneer in Indonesia - Rosilawati, Yeni; Fadilla, Qholifa Yuni (International Journal of Communication and Society, 2022)
Since the President of the Republic of Indonesia, Joko Widodo, announced the first positive case of COVID-19 in Indonesia, the government officially created the COVID-19 Handling Task Force on March 4, 2020. The government has appointed Achmad Yurianto as the Spokesperson for the COVID-19 Handling Task Force. As a spokesperson, Achmad Yurianto conveyed the development of the status issue through the media. However, information ambiguity still arises, creating discretion and negative images of the governmentâ€™s communication style. This research aims to describe how Kompas.com, Republika.co.id, and Detik.com, pioneers of online journalism in Indonesia, framed the news delivered by Achmad Yurianto. In this constructivist paradigm research, the researchers analyzed 28 news samples using the framing model of Pan and Kosicki, then related them to the theory of Social Reality Construction from Berger and Luckmann.Â  At the syntactic structure, the researcher analyzes the facts on the news scheme in the form of headlines, leads, background information, quotes, sources, statements, closings. At the script level, the researcher analyzes the completeness of the news which includes elements of 5W+1H. Furthermore, at the thematic level, the elements of pre-paragraphs and news prepositions. Finally, the researcher looks at the emphasis on facts through grammar, idioms, pictures, graphics in the news. The results disclosed that Kompas.com, Republika.co.id, and Detik.com actively reports the development of information about COVID-19 in Indonesia, including framing the COVID-19 Task Force Handling Spokesperson, Achmad Yurianto. Kompas.com could direct public opinion to see Achmad Yurianto as an arrogant and authoritarian person. Conversely, Detik.com always framed him as a competent and proportionate person in conveying information.